(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
The hospitals of a population are relevant reference point in its history. Its operation is usually extensive over time and in some cases its existence can be comparable to that of the city itself, as happened with the old Esgueva Hospital of Valladolid. In all populations there are usually emblematic hospitals on which for long periods they have been a reference point for the population’s health care. The Hospital Clínico Universitario de Valladolid, if we stick to its performance and activity data, is the most important hospital in the city and had its predecessor in the Provincial and Clinical Hospital, closed for health activity, when the first one was inaugurated. Between them they add a period of activity of 130 years at the present time to which the so-called Resurrection Hospital opened in 1544 would have to be added to perform their functions, which was also closed and demolished when the Provincial was opened and Clinic in 1889, which adds a total of almost 500 years of hospital support in the city of Pisuerga, although curiously the three hospitals to which a room should be added, the Hospital de Esgueva, are linked by proximity of only several meters to the channel from the other river of Valladolid, which is the Esgueva River.